Evaluation of quality of life of patients after rectal surgery - V. I. Pomazkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To evaluate psychometric properties of original «Quality of life after rectal surgery questionnaire».Material and methods. Original study included results of 86 patients rectal cancer in whom the anterior rectectomy has been executed. Investigation was carried out in 3 months after intervention. At 46 patients the level of colorectal anastomosis was higher than 5 cm from anus, in 40 – lower, than 5 cm. An assessment carried out by proposed questionnaire including 34 items with defining of following scales: «General life satisfaction»; «Change of life mode»; «Social functioning»; «Change of psychoemotional status»; “Pain syndrome”; «Anal incontinence»; «Frequency of bowel movements» and «Disorders of evacuatory rectal function».Results. Reliability of questionnaire was shown. Cronbach’s coefficient was higher than 0,7, and quotient of interclass correlation – over 0,8 for each scale. Reproducibility data by test-retest method demonstrated stability of obtained results. Evaluation of design validity proved sufficient sensitivity of the questionnaire. Criterial validity was confirmed by correlation with МOSSF 36 questionnaire scales.Conclusion. Conclusion on eligibility of the proposed «Quality of life after rectal surgery questionnaire» for study of parameters of quality of life of patients after sphincter-preserving operations.